NMR : Tomography, Diffusometry, Relaxometry / by Rainer Kimmich. - Kimmich, Rainer (Springer Berlin Heidelberg, 1997)
Tomography, diffusometry and relaxometry are fields based on common physical principles. The combined use of such techniques provides synergistic insight into physicochemical material properties of an object. The difficulty which newcomers to the field face is to practice and to apply theoretical formalisms from different sources while still learning the principles of NMR and while being already engaged in NMR research. So the author's ambition is a treatise that offers easy and quick access for the reader to any implied matter of interest. He has exerted himself to facilitate the comprehension of NMR principles by extensive cross-referencing among the sections and chapters.